A Technique for Treatment of Overdrainage in Ventriculoperitoneal Shunt - Kpélao, Essossinam; Békéti, Katanga Anthony; Moumouni, Abdel Kader; Hobli-Ahanogbe, Kodjo Mensah; Doléagbenou, Agbéko Komlan; Egu, Komi; ALIHONOU, THIERRY (My University, 2017)
Background and Importance: Overdrainage is a complication of ventriculoperitoneal shunt but adjustable valves and anti-siphon devices can prevent it. These very expensive valves are most often inaccessible, so that the majority of the valves available in Togo are fixed differential pressure valves. Although overdrainage is a widely-known issue, we aimed to introduce a new risk factor and the way we manage this complication. Case Presentation: This case series study included all patients who had overdrainage or a high potential risk of overdrainage (hydranencephaly). Our technique consisted of partial ligation of the peritoneal catheter at the level of the thorax by non-resorbable wire while controlling the drainage rate at the slots. The goal was to transform this fixed differential pressure valve into a pressure-controlled and flow-regulated one. Patients were followed for 1, 3 and 6 months, postoperatively. Conclusion: Hydranencephaly predisposes patients to overdrainage. The partial ligature of the catheter is an effective technique for treating or preventing overdrainage.
Keywords: Overdrainage; Ligation; Catheter